Lung Cancer Combination Treatment: Evaluation of the Synergistic Effect of Cisplatin Prodrug, Vinorelbine and Retinoic Acid When Co-Encapsulated in a Multi-Layered Nano-Platform - Liang Z; Li J; Zhu B (Dove Medical Press, 2020)
Zhen Liang,1 Juan Li,2 Budong Zhu2 1Department of Thoracic Surgery I, Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education), Peking University Cancer Hospital and Institute, Beijing, 100142, People’s Republic of China; 2Key laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Day Oncology Unit, Peking University Cancer Hospital & Institute, Beijing 100142, People’s Republic of ChinaCorrespondence: Budong Zhu Key laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Day Oncology Unit, Peking University Cancer Hospital & Institute, No. 52 Fu-Cheng Road, Hai-Dian District, Beijing 100142, People’s Republic of ChinaEmail zhubdbju@163.comPurpose: Lung cancer remains the leading cancer-associated deaths worldwide. Cisplatin (CIS) was often used in combination with other drugs for the treatment of non-small cell lung cancer (NSCLC). Prodrug is an effective strategy to improve the efficiency of drugs and reduce the toxicity. The aim of this study was to prepare and characterize CIS prodrug, vinorelbine (VNR), and all-trans retinoic acid (ATRA) co-delivered multi-layered nano-platform, evaluating their antitumor activity in vitro and in vivo.Methods: Cisplatin prodrug (CISP) was synthesized. A multi-layered nano-platform contained CISP, VNR and ATRA were prepared and named CISP/VNR/ATRA MLNP. The physicochemical properties of CISP/VNR/ATRA MLNP were investigated. In vitro cytotoxicity against CIS-resistant NSCLC cells (A549/CIS cells) and Human normal lung epithelial cells (BEAS-2B cells) was investigated, and in vivo anti-tumor efficiency was evaluated on mice bearing A549/CIS cells xenografts.Results: CISP/VNR/ATRA MLNP were spherical particles with particle size and zeta potential of 158 nm and 12.3 mV. CISP/VNR/ATRA MLNP (81.36%) was uptake by cancer cells in vitro. CISP/VNR/ATRA MLNP could significantly inhibit the in vivo antitumor growth and suspended the tumor volume from 1440 mm3 to 220 mm3.Conclusion: It could be concluded that the CISP/VNR/ATRA MLNP may be used as a promising system for lung cancer combination treatment.Keywords: lung cancer, combination treatment, synergistic effect, cisplatin prodrug, multi-layered nano-platform